New Treatment Strategies in the Treatment of Juvenile Idiopathic Arthritis - İbrahim GÖKÇE,; Erkan DEMİRKAYA, (Archives of Rheumatology, 2011)
Juvenile idiopathic arthritis (JIA) is the most common chronic rheumatic disease in childhood with an incidence of 10-19/100.000 children below the age of 16 years, and it is also one of the major causes of acquired disability and impairment of quality of life in childhood. Early and aggressive control of arthritis is essential to prevent long-term disability. Methotrexate (MTX) provides clinical benefits in JIA with an acceptable profile of toxic effects. Nevertheless, in many cases, inefficacy, especially in patients with polyarticular and systemic-onset form of JIA (SOJIA) or intolerance to MTX, has led investigators to try other therapeutic options. Biologic agents have been designed to target key cytokines implicated in JIA including tumor necrosis factor-α (TNF-α), Interleukin-1 (IL-1), IL-6 as well as signaling molecules involved in the regulation of T-cell and B-cell lympocyte responses. Up to now, the U.S. Food and Drug Administration (FDA) has approved three biologic agents for use in moderate to severe polyarticular JIA: etanercept, adalimumab and abatacept. In general, TNF-α inhibitors are more beneficial for children with polyarticular disease, and the biological agents that target IL-1 and IL-6 activity appear to be successful also in treating patients with SOJIA. The T-cell costimulation modulator, abatacept, was shown to be effective for the treatment of patients with moderate to severe polyarticular JIA. Autologous stem cell transplantation has also been used in patients with refractory JIA; however, the procedure carries the risk of treatment-related high morbidity and mortality. The purpose of this review is to summarise the recent advances in the treatment of JIA.